Reflectance characteristics of silicon surface fabricated with the arrays of uniform inverted pyramid microstructures in UV-visible range - Mohd Faizol Abdullah,; Abdul Manaf Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this paper, inverted pyramidal microstructures are designed and fabricated on silicon (Si) surface. The characteristics of surface reflectance are simulated using two-dimensional (2D) finite-difference time-domain (FDTD) method by varying the spacing (S) and width (W) of the pyramidal microstructures. The results showed that the effect of S is more significant compared to W where the reflectance of the irradiated light has been increased gradually with the increase of S from 0 to 3 μm, and the difference is around 9.6%. Due to the etching constraint, S= 3 μm is chosen for the fabrication. Textured structure is fabricated by the anisotropic etching of tetramethyl-ammonium hydroxide (TMAH) with additional of isopropyl alcohol (IPA). Long etching time of 120 min is required to form uniform arrays of pyramidal microstructures with smooth and well-terminated four sidewalls at (111) plane. Due to the undercut etching under SiO2 mask, it results to the formation of slightly larger W and smaller S in the fabricated structures. The measured average reflectance in UV-visible range for the Si with inverted pyramidal microstructures is very low down to 10.4%. The discrepancy between the measured and simulated values is speculated to be due to the use of 2D FDTD instead of three-dimensional (3D) FDTD.